Implementation of Perioperative Music Using the Consolidated Framework for Implementation Research. (September 2018) - Carter, Jessica E.; Pyati, Srinivas; Kanach, Frances A.; Maxwell, Ann Miller W.; Belden, Charles M.; Shea, Christopher M.; Van de Ven, Thomas; Thompson, Jillian; Hoenig, Helen; Raghunathan, Karthik
Abstract : BACKGROUND: Complementary integrative health therapies have a perioperative role in the reduction of pain, analgesic use, and anxiety, and increasing patient satisfaction. However, long implementation lags have been quantified. The Consolidated Framework for Implementation Research (CFIR) can help mitigate this translational problem. METHODS: We reviewed evidence for several nonpharmacological treatments (CFIR domain: characteristics of interventions) and studied external context and organizational readiness for change by surveying providers at 11 Veterans Affairs (VA) hospitals (domains: outer and inner settings). We asked patients about their willingness to receive music and studied the association between this and known risk factors for opioid use (domain: characteristics of individuals). We implemented a protocol for the perioperative use of digital music players loaded with veteran-preferred playlists and evaluated its penetration in a subgroup of patients undergoing joint replacements over a 6-month period (domain: process of implementation). We then extracted data on postoperative recovery time and other outcomes, comparing them with historic and contemporary cohorts. RESULTS: Evidence varied from strong and direct for perioperative music and acupuncture, to modest or weak and indirect for mindfulness, yoga, and tai chi, respectively. Readiness for change surveys completed by 97 perioperative providers showed overall positive scores (mean >0 on a scale from −2 to +2, equivalent to >2.5 on the 5-point Likert scale). Readiness was higher at Durham (+0.47) versus most other VA hospitals (range +0.05 to +0.63). Of 3307 veterans asked about willingness to receive music, approximately 68% (n = 2252) answered "yes." In multivariable analyses, a positive response (acceptability) was independently predicted by younger age and higher mean preoperative pain scores (>4 out of 10 over 90 days before admission), factors associated with opioid overuse. Penetration was modest in the targeted subset (39 received music out of a possible 81 recipients), potentially reduced by device nonavailability due to diffusion into nontargeted populations. Postoperative recovery time was not changed, suggesting smooth integration into workflow. CONCLUSIONS: CFIR-guided implementation of perioperative music was feasible at a tertiary VA hospital, with moderate penetration in a high-risk subset of patients. Use of digital music players with preferred playlists was supported by strong evidence, tension for change, modest readiness among providers, good acceptability among patients (especially those at risk for opioid overuse), and a protocolized approach. Further study is needed to identify similar frameworks for effective knowledge-translation activities.